2017
DOI: 10.1002/bdr2.1001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Antibodies to Chlamydia trachomatis and Risk of Gastroschisis

Abstract: Background Gastroschisis, a birth defect of the abdominal wall, is increasing in prevalence. The largest increase in prevalence has been observed among young mothers (<20 years). The prevalence of Chlamydia trachomatis (CT) infection is highest among young women and has also been increasing over time. The objective was to investigate the association between immunoglobulin G antibodies to Chlamydia trachomatis (CT) (anti-CT) and Chlamydial heat shock protein 60 (anti-CHP60) during pregnancy, and risk of gastros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…A recent study21 noted a fourfold increased risk for gastroschisis among women with seropositivity during pregnancy to anti- C. trachomatis IgG 3 , suggesting a role for recent STI due to C. trachomatis . However, in a Finnish cohort, no association was observed between C. trachomatis- specific IgG and gastroschisis,22 though a twofold increased risk was observed with presence of antibodies to herpes simplex virus type 2 (HSV-2) during early pregnancy 23…”
Section: Introductionmentioning
confidence: 99%
“…A recent study21 noted a fourfold increased risk for gastroschisis among women with seropositivity during pregnancy to anti- C. trachomatis IgG 3 , suggesting a role for recent STI due to C. trachomatis . However, in a Finnish cohort, no association was observed between C. trachomatis- specific IgG and gastroschisis,22 though a twofold increased risk was observed with presence of antibodies to herpes simplex virus type 2 (HSV-2) during early pregnancy 23…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that these columnar cells become squamous with increasing age, which decreases the pathogen-cell affinity and the probability of infection. The results of Feldkamp et al 31 differ from those previously published by Parker et al 33 , for the first trimester of gestation, in that the latter found no association between reactivity in terms of IgG against the pathogen or against the chlamydial heat shock protein CHP60, which should reflect the chronicity of the infection with Chlamydia trachomatis .…”
Section: Infectious Agentsmentioning
confidence: 55%
“…However, taking into account that until a few decades ago women were mothers at an early age but there was no growing global prevalence that the malformation currently shows 30 , maternal age must be considered simultaneously with other prevalent factors in very young women, related to exposure to various exogenous agents such as tobacco, alcohol or illicit drugs, as well as the early initiation of sexual activity and the acquisition of genitourinary infections. In this regard, epidemiological findings have shown that infections acquired shortly before or during the first trimester of gestation, such as urinary and sexually transmitted infections, are similarly associated with gastroschisis, possibly through a pathway that involves the immune response 31 - 33 . In a case-control study, Feldkamp et al 31 , reported that the risk of malformation doubled and even increased up to 25 times in the case of maternal age less than 20 years or smoking.…”
Section: Origin Of Gastroschisismentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that this pathogenic effect of CT infection may also play an important role in stillbirths (7,23). CT antibodies were reported to be higher in mothers who had stillbirths compared to mothers with live births (4,7,(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%